Pregnancy in autistic women and social medical considerations: scoping review and meta- synthesis - Ferrara, Rosaria; Ricci, Pasquale; Damato, Felice Marco; Iovino, Leonardo; Ricci, Lidia; Cicinelli, Giovanni; Simeoli, Roberta; Keller, Roberto (Frontiers in Psychiatry, 2023)
This article addresses a topic that has been largely overlooked by scientific literature, namely pregnancy in autistic women. Generally, the issue of sexuality in disability, particularly in disabled women, autistic or otherwise, has been underexplored. However, it is necessary to scientifically investigate this topic to propose adequate social and health policies. Therefore, we chose to conduct a scoping review to answer three main questions: "What does it mean for an autistic woman to be pregnant?"; "How do these two conditions coexist?"; "Are health services prepared to receive this population adequately or does autism become a stigma for pregnant women?". Methods: We conducted a systematic review and qualitative thematic synthesis following the Preferred Reporting Guidelines for Systematic Reviews and Meta-Analyses on autistic women and pregnancy in the last 10 years. Results: The studies included in our review are 7, extremely diverse in terms of methodologies and sample sizes. Despite the heterogeneity of samples and methodologies, all research tends to highlight the following results. For autistic women during pregnancy, three areas seem to be the most difficult: sensory issues, mood disorders, and relationships with specialists. Discussion: Our study found that women with ASD face unique challenges during childbirth that differ from those of neurotypical women. Participants often felt belittled, ignored, and uninformed about the care they received, and being placed at the centre of attention was often seen as negative and hindering rather than positive. However, the research shows us how some "expected" results, such as difficulties in breastfeeding, have been disproven.